(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Since Nigeria’s universities are responsible for cultivating the country’s workforce, the decline in their quality has a knock-on effect on the country’s social, economic, and technological advancements. In response to this issue, several organisations have been established to provide quality assurance in educational institutions. Many obstacles have been placed in the path of these organisations. The purpose of this article is to investigate the obstacles standing in the way of a successful quality assurance programme in Nigeria’s publicly funded institutions of higher learning. In order to back up their claims, the authors used secondary sources in their research. Sorted and utilised in the paper were sources from both print and internet media. Inadequate funding, scarcity of academic staff, poor execution of quality control policies, insufficient infrastructural amenities, brain-drain, strike actions, corruption, weak oversight, and poor staff development are all issues that have been identified in this paper as impediments to quality assurance in Nigerian higher institutions. It has been proposed that the following measures be taken to ensure quality in Nigeria’s higher institutions: sufficient funding, adequate employment of academic staff, provision basic infrastructures, fight against all forms of bribery, implement all agreements reached with the various union groups, encourage academic staff, direct monitoring, and effective staff growth